Melanoma tumors frequently acquire LRP2/megalin expression, which modulates melanoma cell proliferation and survival rates. (13th February 2015) - Andersen, Rikke K.; Hammer, Katrine; Hager, Henrik; Christensen, Julie N.; Ludvigsen, Maja; Honoré, Bent; Thomsen, Mai‐Britt H.; Madsen, Mette
Summary We show that the multiligand receptor megalin, known to mediate uptake and trafficking of nutrients and signaling molecules, is frequently expressed in malignant melanoma samples. Expression of megalin‐encoding mRNA was investigated in 65 samples of nevi, melanomas, and melanoma metastases and was observed in more than 60% of the malignant samples, while only in 20% of the benign counterparts. Megalin expression in nevus and melanoma samples was additionally investigated by immunohistochemistry, which confirmed our mRNA‐based observations. We furthermore show that a panel of tumor‐derived melanoma cell lines express LRP2/megalin endogenously. In these cells, megalin is internalized from the cell surface and localizes extensively to intracellular vesicles, confirming receptor activity and pointing toward association with the endocytic apparatus. Groundbreaking, our results indicate that sustained megalin expression in melanoma cells is crucial for cell maintenance, as siRNA‐mediated reduction in melanoma cell expression of LRP2/megalin significantly decreases melanoma cell proliferation and survival rates.